Pengaruh Kualitas Pelayanan dan Kepuasan Terhadap Loyalitas Pasien Klinik Eksekutif Raflesia Di Rumah Sakit Umum Daerah Pasar Rebo, Jakarta Timur - Baiq Dina Ferdiyanti; Ade Firmansyah (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.Quality healthcare services have become a primary demand of the public, requiring hospitals not only toprovide accurate and prompt medical care but also to create a satisfying experience while fostering patienttrust and loyalty. This study aims to analyze and evaluate the influence of service quality and patientsatisfaction, both partially and simultaneously, on patient loyalty at the Rafflesia Executive Clinic, PasarRebo Regional General Hospital (RSUD), East Jakarta. A quantitative approach was employed usingquestionnaires distributed through a non-probability sampling method. The study population consisted of7,529 individuals, with a sample of 100 respondents determined using Cochran's formula. Based on theresearch findings, it was concluded that service quality had a partial effect on patient loyalty by 34.8%, andpatient satisfaction had a partial effect by 37.7%. Simultaneously, both variables influenced patient loyaltyby 43.6%, while the remaining 56.4% was affected by other factors beyond the scope of this study. It is recommended that the Rafflesia executive clinic improve staff competencies in understanding patient needs, regularly evaluate and ensure the implementation of quality service standars, and build long-term trust andrelationships with patients to reduce the tendency of switching to other healthcare facilities.Keywords: Service Quality, Patient Satisfaction, Patient Loyality